Efficiency of turkish provincial general hospitals with mortality as undesirable output - (:unkn) unknown (IGI Global, 2013)
The authors present a directional distance model where quality of care is brought in by treating mortality in each hospital as a strongly disposable "bad output." After deriving pure technical and scale inefficiencies under strong disposability, the authors derive "congestion" inefficiencies via allowing weak disposability. A second stage, "seemingly unrelated" regression of these inefficiencies against hospital level variables like spare capacity, inpatient-to-outpatient ratio, and bed turnover rate allows pinpointing the critical areas for hospital performance improvement. Evidence shows that the smallest hospitals are operating on an inefficient scale. Moreover, allocation of specialists should be done very carefully, as shortage of specialists seems to cause congestion inefficiency, while having too many specialists causes technical inefficiency. © 2013, IGI Global.